Censorship detected in AE (United Arab Emirates) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in United Arab Emirates. Data sourced from OONI.
Censorship Incident ID: AE-2026-1415. Severity: critical. Confidence: 90%